2009
DOI: 10.1016/j.clinph.2009.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between preattentive sensory processing deficits and age in schizophrenia patients

Abstract: Objective-Auditory mismatch negativity (MMN) and P3a index preattentive detection of rare stimuli. Their amplitudes normally decrease with age. Previous studies have reported generally smaller than normal MMN and P3a in schizophrenia patients. We aimed to further characterize the course of these deficits over schizophrenia patients' lifespan.Methods-In 253 schizophrenia patients and 147 normal comparison participants (NCPs) encompassing a wide age range (18-65), event-related potentials were recorded while par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 67 publications
(80 reference statements)
7
75
2
2
Order By: Relevance
“…Mismatch negativity (MMN) and its magnetic counterpart (MMNm) are useful electrophysiological markers to evaluate the integrity of automatic central auditory processing (Hsiao, Cheng, Liao, & Lin, 2010;Kujala, Tervaniemi, & Schroger, 2007;Naatanen et al, 2011;Yabe et al, 2004). A number of studies have reported a lower amplitude of MMN/MMNm in response to pure-tone stimuli in aged adults (Alain, McDonald, Ostroff, & Schneider, 2004;Cheng, Baillet, Hsiao, & Lin, 2013;Cheng, Hsu, & Lin, 2013;Cheng, Wang, Hsu, & Lin, 2012;Cooper, Todd, McGill, & Michie, 2006;Czigler, Csibra, & Csontos, 1992;Kiang, Braff, Sprock, & Light, 2009), while to our knowledge, little is known about the effects of aging on the early cortical processes of phonetic discrimination.…”
Section: Introductionmentioning
confidence: 94%
“…Mismatch negativity (MMN) and its magnetic counterpart (MMNm) are useful electrophysiological markers to evaluate the integrity of automatic central auditory processing (Hsiao, Cheng, Liao, & Lin, 2010;Kujala, Tervaniemi, & Schroger, 2007;Naatanen et al, 2011;Yabe et al, 2004). A number of studies have reported a lower amplitude of MMN/MMNm in response to pure-tone stimuli in aged adults (Alain, McDonald, Ostroff, & Schneider, 2004;Cheng, Baillet, Hsiao, & Lin, 2013;Cheng, Hsu, & Lin, 2013;Cheng, Wang, Hsu, & Lin, 2012;Cooper, Todd, McGill, & Michie, 2006;Czigler, Csibra, & Csontos, 1992;Kiang, Braff, Sprock, & Light, 2009), while to our knowledge, little is known about the effects of aging on the early cortical processes of phonetic discrimination.…”
Section: Introductionmentioning
confidence: 94%
“…A fenti megfigyelésnek azonban ellentmond, hogy az N100 differenciáldiagnosztikai értéke nagy lehet: más hullámformák eltéréseivel összevetve az N100 amplitúdójának variációja a SZ-val diagnosztizált betegeket 79%-os, illetve 72%-os valószínűséggel különítette el az egészséges személyektől és a bipoláris zavart (BZ) mutató csoporttól 4 . fokozatos csökkenését a betegség lefolyása során több tanulmány is alátámasztja 5,7,12 . Ennek megfelelően a csökkent amplitúdójú hosszdeviáns EN pszichotikus tüneteket már megélt betegeknél a betegség kezdeti fázisában is jelen van 13 , illetve pszichésen egészséges rokonaiknál is megfigyelhető 14 .…”
Section: N100 Habituációunclassified
“…A P3a amplitúdója nem változik a betegség hosszával, stabil funkcióvesztésnek mondható 12 , már a magas rizikójú csoportokban és első pszichotikus epizód idején is kimutatható 8,10 , ill. nem korrelál a tünetbecslő skálák értékeivel 13 . A legtöbb vizsgálat szerint a P3b amplitúdó csökkenése SZ-ben annyira stabil jellemző, hogy endofenotípus is lehet.…”
Section: P300unclassified
“…Numerous studies provide evidence for age-related deficits in temporal processing at the level of ASM (for review: Cheng et al, 2013; Näätänen et al, 2011a; Pekkonen, 2000). Older adults show impaired ASM processing for detection of changes in the durations of tones (Karayanidis et al, 1995; Kiang et al, 2009; Pekkonen et al, 1996; Schroeder et al, 1995; Woods, 1992); interstimulus-intervals (Kisley et al, 2005); and short gaps in tones (Alain et al, 2004; Bertoli et al, 2002). These deficits are generally manifest in reduced MMN amplitude in older compared to younger adults.…”
Section: Age-related Deficits In Sensory Memory Processingmentioning
confidence: 99%